A Ministry of Public Health for Ireland - Cox, Michael F. (Statistical and Social Inquiry Society of Ireland, 1919)
Never, perhaps, so much as now has it been fully realised that the most important and most enduring wealth of a State depends upon the health and strength, the strong arms and trained brains of a people. Men of the highest grade of health?of grade "A"?are to be specially sought for, to guard the well-being and the safety of their country. This is recognised by all, from the Prime Minister downwards. Recognising the importance of the preservation of the health and strength of the people, a Ministry of Health is about to be provided for England, and no doubt for Wales and Scotland, whilst Ireland is excluded from the benefits to be conferred on the sister countries.
Read February 28th, 1919
Keywords: Public health; Health reform; 314.15